Implication of Social Media Technology (SMT) for Teaching and Learning in Higher Education - Jong, S.J; Hafizan, M.N; Ang, T.C; Chong, C.C (Universiti Malaysia Sarawak, UNIMAS, 2014)
We have reached a new era of teaching and learning that are student-centered, technologically mediated and social rich media. Social media has gained the attention in the community of teaching and learning in Higher Education. It allows timely end-user engagement at low cost with high efficiency as compared to traditional communication tools. Nevertheless, it has subtly directing a new way we inquire and process information. This study aims to identify the implication of social media in enhancing teaching and learning of Information and Communication Technology (ICT) courses in Higher Education. We investigate how social media could promote Self-Directed Learning (SDL) and its impact in learning process among UNIMAS students through online survey. Focus group interviews with academic with diversity background were conducted to study the implementation of social media in their teaching practices. This study serves as a building block to understand the academic and learners‟ perceptions of using social media in teaching and learning in UNIMAS.